Intensive Variable and Its Application - Zheng, Xinqi; Xue, Chunlu; Yuan, Zhiyuan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
There are still insufficient general theories on the law of diminishing returns, despite 100 years of development. Starting with intensive variables theory, and by utilizing tools of spatiotemporal correlation and intensive functions, moving on to the integrated curve of diminishing returns and intensive theory, and even more importantly, using a combination of static and dynamic GIS, and integrating numerical calculation and spatial optimization, this book not only creates a unique theoretical framework and methodology for the evaluation of land use effect, but also addresses the long-standing lack of universal theories and methods on the law of diminishing returns. It will have far-reaching impacts on the development of this area and its practical application. The book covers a wide range fields in geography, land science, geographic information science, management science and related areas. Novel theoretical perspectives illustrated with many detailed case studies offer an easier way for readers to expand their research, ensuring that both academic and business audiences will benefit. Prof. Xinqi Zheng works at the China University of Geosciences (Beijing), People$1 (Bs Republic of China.s
Introduction -- The IV Theory -- IV methodology -- Computing tools -- Intensive Evaluation of Regional Land Use -- Intensive evaluation of urban land use -- Conclusion and Outlook.
Keywords: Geography; Econometrics; Geography; Geography, general; Econometrics; Environmental Monitoring/Analysis.; Electronic books